Induction of apoptosis by essential oil of Dracocephalum kotschyi on Trichomonas vaginalis. Issue 2 (17th October 2022) - Chelgerdi Dehkordi, Bahareh; Esmaeilifallah, Mahsa; Kalantari, Reza; Benchimol, Marlene; Khamesipour, Faham
Abstract: Background: Trichomonas vaginalis is a protist parasite that causes trichomoniasis, a sexually transmitted disease. Metronidazole is the current treatment for trichomoniasis. However, this drug can provoke severe side effects, and some strains present resistance, making the development of alternative treatments for trichomoniasis urgent. Objectives: We investigate the use of essential oil obtained from Dracocephalum kotschyi on T. vaginalis . D. kotschyi has antispasmodic and analgesic properties and is well known in Iran. Methods: The essential oil was obtained by hydrodistillation from 1000 g of the powdered plant. Gas chromatography‐mass spectrometry analysis was used for the chemical composition of the essential oil, and 11 substances were identified, corresponding to 91.5% of the oil. Copaene (22.15%), Methyl geranate (16.31%), Geranial (13.78%) and Carvone (11.34%) were the main substances. A cell viability test was used to determine the percentage of growth inhibition (GI%) and the half‐maximal inhibitory concentration (IC50) on T. vaginalis after incubation with the prepared essential oil. Results: The oil induced an IC50 of 84.07 µg/ml after 24 h contact with trophozoites. Cytotoxicity was determined by MTT assay on the J774.A1 haematopoietic cell line. In addition, the initial stage of apoptosis was assayed using the fluorescein isothiocyanate Annexin V Apoptosis Detection Kit. Evaluation of the in vitro anti‐trichomonal properties of D. kotschyi essential oils showed that it effectively induces apoptosis on T. vaginalis between 100 and 700 µg/ml after 48 h without toxicity on haematopoietic cells, suggesting that D. kotschyi essential oil can induce programmed death in T. vaginalis . Conclusions: The anti‐trichomonal properties of D. kotschyi essential oil indicate that they could be suitable for new pharmacologic studies after new tests with human vaginal epithelial cells. Abstract : The anti‐trichomonal properties of D. kotschyi essential oil indicate that they could be suitable for new pharmacologic studies after new tests with human vaginal epithelial cells.